Juxta articular osteoid osteoma of the calcaneum: a rare case report - Upadhyay, Gunjan (International Journal of Research in Orthopaedics, 2020)
Osteoid osteoma of calcaneum in a juxta-articular position is a rare finding, it is most often misdiagnosed. It mimics as arthritis. Osteoid osteoma is benign bone neoplasia mostly in male in 2nd - 3rd decade of life. It has typical features of night pain relieved with salicylates. 35 years old female present with right heel pain. Mother has positive history of rheumatoid arthritis. X-ray and computer tomography were done for diagnosis. Diagnosis was made of juxta –articular position of osteoid psteoma in the calcaneum. Lesion was excised after pre-anesthesia checkup and sent for histopathology. Once investigation was done diagnosis was made as an osteoid osteoma in juxta articular position of calcaneum. Treated by excision of the lesion surgically and specimen sent for biopsy which confirm osteoid osteoma.